QUANTIFICATION OF QUERCETIN AND CHLOROGENIC ACID IN PAPAYA SEED ETHANOL EXTRACT - RATIH PUSPORINI; HANAA OMAR BAABDULLAH; ANDYKA, VERU (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to quantify the quercetin and chlorogenic contained in the ethanolic extract of papaya seed. Methods: Papaya seeds were extracted using the maceration method; then, the qualitative phytochemical analysis was obtained from standard phytochemical screening; furthermore, liquid chromatography–mass spectrometry (LC–MS) examination was used to determine the number of its bioactive compounds. Results: The quantitative examination using LC–MS showed that the content of chlorogenic acid was greater than the quercetin level. Further studies have to be carried out regarding the papaya seed ethanolic extract in vitro inhibition compare to the antibacterial potential of the commercial antibiotics on the tested bacteria species. Conclusion: Our results suggest that papaya seed ethanolic extract quantitatively contains chlorogenic acid greater than quercetin.